FEMALE READERS' PERCEPTION OF CODE SWICHING PHENOMENON ON GURU IN GIRLFRIEND MAGAZINES - Qisti Triani, - (2011)
This paper entitled "Female Readers' Perception of Code Switching Phenomenon on Guru rubric in Girlfriend magazine" examines readers' perception, the function, advantages and disadvantages of the use of code switching in the magazine. The present study used a descriptive qualitative method. The data were collected through three instruments: closed ended questionnaire, open-ended questionnaire, and interview. The respondents of this study were twenty female students taken from English and non-English department. The results show that all respondents (100%) positively perceived the code switching occurrences on Guru rubric. Regarding the function of code switching, only five functions were identified: emphasis (75%), quotation (50%), reiteration (70%), untranslatability (55%), and parenthesis (80%). Parenthesis was found to be the most frequent function perceived by the readers (80%). Moreover, the findings also reveal that the respondents had perceived some advantages and disadvantages of code switching. The advantages involve the attraction and boredom avoidance when reading the articles, as well as introducing English common utterances, increasing English vocabulary, and showing the main points of the articles. In contrast, the disadvantages were that the code switching brings about confusion due to different grammatical pattern between English and Indonesian and for readers who did not understand English, the code switching lessens their reading enjoyment.